Dietary Composition and Functional Properties of Selected Watermelon Seeds Available in Bangladesh (SAARC Journal of Agriculture, 2022)
This study was carried out to investigate the nutritional composition and functional properties of two varieties of watermelon seeds and compare these properties between these seeds for harnessing them for consumption as food. The dried seeds of the two types of watermelon were evaluated by using a standard method for different characteristics such as nutritional, phytochemical and functional properties to perceive the potential benefits of that seed. The result of nutritional composition and phytochemical compound analysis obtained for the two varieties (Crimson red and Charleston gray) of watermelon seed indicated that both varieties of watermelon seed were rich in energy (469.60±0.01Kcal/100g, 408.85±0.01Kcal/100g), crude fat (36.61±0.01%, 30.65±0.01%), crude protein (27.21±0.01%, 22.51±0.01%), fiber (21.55±0.01, 29.85±0.01%) and phytochemical compound such as crude alkaloid (14.05±0.006%, 10.56±0.006%) respectively. The study result showed that, the crude fat, crude protein, energy and crude alkaloid were found to be high in the amount in the Crimson red seed than Charleston gray seed. Whereas the crude fiber was the high amount in the Charleston gray seed compared to the Crimson red seed. Functional properties may impact the behavior of food protein during processing, formulation and storage. The functional properties such as water absorption capacity, oil absorption capacity, emulsion activity, emulsion stability, foam activity, and foam stability were analysed of two varieties of watermelon seeds. The present research study revealed that both the two varieties of watermelon seed are characterized with good functional properties which indicate that the watermelon seeds can be incorporated in the formulation of food for consumption and use for industrial purposes.SAARC J. Agric., 19(2): 233-243 (2021)